Formulation And Physical Evaluation of Body Scrub Cream From 95% Ethanol Extract of Breadfruit Peel (Artocarpus altilis) as Antioxidants - Meta Safitri; Arini Aprilliani; Mohammad Zaky; Siti Mukammila Azkiya (Universitas Airlangga, 2024)
Background: Breadfruit (Artocarpus altilis) peel contains many chemical compounds including alkaloids, flavonoids, saponins, polyphenols, and steroids/terpenoids. Breadfruit peel has potential as an antioxidant because it contains phenolic compounds, especially flavonoids and polyphenols. Objective: The aim of this study was to formulate and physically evaluate the preparation of a scrub cream from a 95% ethanol extract of breadfruit peel (Artocarpus altilis) and test its antioxidant activity. Methods: Body scrub cream formulations were prepared using different extract concentrations, such as F1 (no extract), F2 1%, F3 3%, F4 5%, and F5 (Vit C as an equalizer for the antioxidant activity test). Body scrub cream was formulated as an oil-in-water type cream preparation using breadfruit starch as a scrub. Physical evaluation of this preparation consisted of organoleptic, homogeneity, viscosity, pH, spreadability, adhesiveness, and room-temperature storage tests. The antioxidant activity was evaluated using the DPPH method. Results: The results of the physical evaluation test showed that the body scrub cream produced good results and complied with the requirements of cream products. Antioxidant activity test results show the IC50 value of each formula is F1 (without extract) 107.8 µg/mL, F2 (1%) 72.48 µg/mL, F3 (3%) 56.54 µg/mL, F4 (5%) 43.40 µg/mL and F5 (vitamin C K+) 38.94 µg/mL. Conclusion: Based on these observations, the best formula is Formula 3 because the antioxidant test results are classified as strong, and the physical evaluation tests are considered stable.